Battery performance evaluation of solar assistive electric vehicle - Neupane, Sudan; Joshi, Pankaj; Badu, Subas; Kalauni, Rohit Kumar; Rajak, Bijay Prakash (Journal of Innovations in Engineering Education, 2022)
Solar powered electric vehicles have great opportunities on obtaining a clean, self-sufficient, inexhaustible and free source of energy that could get better of energy crisis in automobile industry. Any means that could generate electricity in both running and static condition not only lessen the charging time but also help in efficient battery performance. Accordingly, solar powered vehicle solves many problems related to the environment and is the best pollution free method. This project focuses on charging and discharging pattern of battery of an electric trike with and without solar assistance. This article provides detail comparison of battery performance between a solar assisted trike and pure electric trike. This experiment mainly incorporates charging assisted with help of solar panel mounted on top of electric vehicle.